(untitled) (Damascus University Journal of agriculture sciences, 2022)
The present study was carried out to determine the chemical composition of essential oil of aerial part of Marigold (Tagetes patula L.) The aerial parts were collected, during 2017, and the essential oil process was conducted with Clevenger,s apparatus. and analyzed using Gas Chromatography- Mass Spectrometry (GC/MS). In total, 16 compounds were identified in the essential oil the of Marigold. The major components were, Limonene (7.52%), α-Terpinolene (9.23%), trans-caryophyllene (11.89%), Caryophyllene oxide (8.87%), Neophytadiene(9.65), Palmatic acid(4.33%) and Phytol (6.23%). The toxicity of evaporate from essential oil of Marigold against adult of cowpea weevil (Callosobruchus maculates (Coleoptera) and adult of Mediterranean flour moth (Ephestia kuehniella Zeller :Lepidoptera) was studied. The essential oil from Marigold was used as fumigant at doses of concentration 5,1015,20,25,30,35,40,45,50µl/L air. The result obtained showed that the fumigant toxicity of the essential oil increased significantly with the increase in the concentration.The efficacy of the oil was higher on the flour moth than the weevil, as reflected by its LC50 of 15.06 and 20.92 µl/L air at 48 incubation periodd, respectively. Also, The antifungal activity of the methanol extract of Marigold was tested against fungi species (Aspergillus flavus, Botrytis cinerea, Fusarium oxysporum and Pencillum digitatum.) at concentrations of 50, 100, 150, 200, 250, 500and 1000µl/100ml by using poison food technique. The results indicated that Methanol extract of Marigold was significantly superior antifungal activity to P. digitatum and B. cinerea, where, the ED50 were, 126.48 and 195.24 µl/100ml respectively. and lowest effect was on the F. oxysporum fungus. Therefore it is recommended to use the essential oil and Methanol extract of Marigold as biocide against insects and fungi.